Varstvo ustavnih pravic v postopkih cenitve davčne osnove - Korže, Branko (Podjetje in delo, 2015)
The author discusses the theoretical fundamentals on which tax systems are established in democratic states governed by the rule of law. On the sovereignty of the state and constitutional principles the author justifies the legislator's right when imposing tax burdens on citizens and other members in a relevant relationship with the state and discusses the rights and restrictions of the state in relation to the taxable persons. The article includes the systematic study of the constitutionality of the legislator's regulation of the "tax base assessment" and the justification for the waiver of the fundamental constitutional rights of taxable persons. In this relation, the article looks at the conduct of tax bodies when commencing the proceedings of tax base assessment and that of courts controlling the legality and constitutionality of the conduct of tax bodies as the conduct of the executive branch of the government. The author submits some proposals for the elimination of non-constitutional solutions of the legislator relating to the findings and actions of tax bodies in the proceedings of "tax base assessment" resulting in the risks of violation of human and other constitutional rights of taxable persons. Considering these facts, the author makes an appeal to the legislator to eliminate unconstitutional legal regulations and submits proposals for more efficient protection of legality and constitutionality over the work of tax bodies to the judicial branch of the government.
Keywords: davki; obdavčevanje; pravna država; pravno varstvo; tax; ustavne pravice